The Relationship with Self-efficacy and Motivation Athletes Achievement in Football School (SSB) Posba Basongan - Ficki Qoirul Idzam; Puspodari; Weda (CV. Nusantara Sporta, 2023)
Football is not only physical but also mental. Lack of mentality in young players will emerge with self-efficacy and good motivation to achieve an achievement. The purpose of this study was to determine the relationship between self-efficacy and motivation on the achievements of Posba Bangsongan Kediri athletes. This study used a quantitative approach with a sample of 30 athletes using a total sampling technique. This data analysis technique uses a formula, namely product moment correlation. The results of the study show that 1) there is a positive and significant relationship between self-efficacy and athlete achievement. Evidenced by the sig (2-tailed) value of 0.019 > 0.05, which means that there is a relationship between self-efficacy and athlete achievement. 2) there is a positive and significant relationship between motivation and athlete achievement. It is proved that the sig (2-tailed) value is 0.13 > 0.05 which means there is a relationship between motivation and athlete achievement. 3) there is a positive and significant relationship between self-efficacy and motivation on athlete achievement. Evidenced by the value 1 seen from the correlation coefficient, the magnitude of the correlation coefficient with the basis that is if the value is close to 1 or -1 there is a relationship if it is close to 0 there is a weak relationship, meaning that self-efficacy and motivation with achievement have a very strong relationship